Social media behaviors and body type ideals predict weight loss and food tracking behaviors among recreational climbers - Slagel, Nicholas; Kage, Katie; Wichern, Sarah (Frontiers in Sports and Active Living, 2024)
Introduction -Elite and recreational climbers may be at risk for disordered eating, low energy availability (LEA), and increased injury as a result. Social media use among athlete and non-athletes can lead to body image disturbances resulting in unhealthy weight loss practices exacerbating LEA and injury risk. Therefore, the objective of this study was to examine relationships between social comparative behaviors on social media, body type ideals and outcomes, and health behaviors among adult recreational climbers.Methods -Participants (n=324) were adult recreational climbers from the U.S. (29.30 ± 9.99 years old and 50% female). Participants answered a 66-item questionnaire comprised of demographics, climbing characteristics, social media behaviors, body type ideals, training and nutrition-seeking behaviors, and weight and food tracking behaviors.Results -Most participants (78.7%) indicated strength-to-weight ratio was important for climbing performance. Many participants perceived they could perform better at rock climbing if their body proportions were different (59.3%). These body type ideals were found to be significant predictors of performing weight loss and food-tracking behaviors (all p < .001). Higher amounts of social comparative behaviors on social media and social physique anxiety independently and significantly predicted attempting weight loss to improve climbing ability (p<0.001 and p=0.001 respectively). Those who followed climbing influencers, used Instagram frequently for training and nutrition information, perceived they could perform better at rock climbing if their body proportions were different, or were female and college-aged had significantly higher mean social comparative behavior scores (all p<0.01).Discussion -This study expands on prior work with elite climbers by providing a possible explanation for how climbing-related body type ideals and certain social media behaviors can perpetuate negative body image and compensatory behaviors among a general climbing population. Because unhealthy weight management behaviors can lead to injury and health disturbances, broad education programming and social media campaigns should be developed to shift body ideals and nutrition behaviors among recreational climbers.